The community of disgrace (Maurice Blanchot and Marguerite Duras I.) - Mejía Toro, Jorge Mario (Estudios de Filosofía, 1994)
In La communauté inavouable (1983), Blanchot expressly takes up the subject of thinking about the community of those who have no community, a matter he had already considered in Le livre á venir (1959) and in L'entretien infini (1969). The present lecture refers to those antecedents. In the first part, taking up Duras' narrative Le square (1956) and Blanchot's essay meditating on it, The pain of dialogue, the lecture points to the "ethical" relationship between conversation and disgrace. The second part gives a characterization of the time when the strange occurrence of conversation takes place and, equally, of those experiences permitting thought not to precede disgrace, though not abandoning itself to the absence of thought, either. The third part makes a reading of the pieces called Indestructible, The Relation of the Third Genre, etc., in order to establish the traits of the different "levels" of disgrace relative to the possibility or impossibility of conversation. The fourth and last part returns to the first one, with the purpose of precising the community of those who have nothing in common except their separation -different in each of them- from the world: the community of disgrace.